2022
DOI: 10.3390/molecules27030988
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Synthesis of Copper Phyllosilicates as Effective Catalysts for Hydrogenation of C≡C Bonds

Abstract: For the first time, the new microwave-assisted method for the synthesis of copper phyllosilicates on a commercial SiO2 carrier was developed. The application of microwave synthesis allowed to decrease the synthesis time from 9 to 6 h compared to the traditional DPU method of preparing chrysocolla. The synthesized catalysts were studied by N2 adsorption, TEM and XRD methods. Catalysts prepared by microwave method are highly effective in the selective hydrogenation of the С≡С bond in 1,4-butynediol to 1,4-butene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…At the same time, the authors proposed a methodology for the synthesis of a porous metal−metal oxide catalyst on a carbon carrier for heterogeneous hydrogenation [36]. A new microwave synthesis of copper phyllosilicates on a commercial SiO2 carrier was first developed [37]. This technique allows a significant reduction of the sample synthesis time from 9 h to 6 h relative to the method of thermal decomposition of urea.…”
Section: Synthesis Of Catalysts Using Microwave Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the authors proposed a methodology for the synthesis of a porous metal−metal oxide catalyst on a carbon carrier for heterogeneous hydrogenation [36]. A new microwave synthesis of copper phyllosilicates on a commercial SiO2 carrier was first developed [37]. This technique allows a significant reduction of the sample synthesis time from 9 h to 6 h relative to the method of thermal decomposition of urea.…”
Section: Synthesis Of Catalysts Using Microwave Radiationmentioning
confidence: 99%
“…It was found that the content of Cu gradually decreased with increasing microwave heating temperature, while the content of Ni and Zn increased with increasing microwave heating temperature, as shown in Table 1. This result is explained by the difference in solubility of metal hydroxides and A new microwave synthesis of copper phyllosilicates on a commercial SiO 2 carrier was first developed [37]. This technique allows a significant reduction of the sample synthesis time from 9 h to 6 h relative to the method of thermal decomposition of urea.…”
Section: Synthesis Of Catalysts Using Microwave Radiationmentioning
confidence: 99%
“…[27] Among the different non-noble metal-based catalytic systems, the hydrosilicate materials -natural minerals, which can be obtained synthetically, are actively used in heterogeneous catalysis. [28] Copper phyllosilicates (PhylS) with the chrysocolla-like structure Cu 2 Si 2 O 5 (OH) 2 • xH 2 O were shown to be the precursors of active catalysts for hydrogenation of esters [29,29,30] and alkynes, [31] as well as for the hydrogenolysis processes. [8,32,33] Recently, we have shown that the copper phyllosilicate based materials are active catalysts in a liquidphase hydrogenation of different nitro-arenes, [34] including even dinitro-and trinitrobenzene.…”
Section: Introductionmentioning
confidence: 99%